PENGARUH PENGGUNAAN MEDIA SOSIAL, WORD OF MOUTH MARKETING DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA DISTRO MUTIMUV STORE SAMARINDA - Fitri Yani (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
In this study, there are four variables, namely Social Media (X1), Word Of Mouth Marketing (X2), Trust (X3) and Purchasing Decision (Y) variables at Mutimuv Store Samarinda Distro. The purpose of this study was to determine and test the effect of the use of social media, word of mouth marketing and trust on purchasing decisions at the Mutimuv Store Samarinda distribution, either partially or simultaneously. The analysis tool used is multiple linear regression with the help of statistical software SPSS version 25.0. The sampling technique in this study is an accidental sampling technique based on who was found when the author conducted the research and the sample used was 75 consumers at the Mutimuv Store Samarinda Distro. This research is a survey research, in which the information collected from respondents using a questionnaire. The method used in this research is quantitative method. The results showed that Social Media, Word of Mouth Marketing and Trust together had a significant influence on purchasing decisions at Mutimuv Samarinda Distro. These results mean that variations in purchasing decisions are jointly influenced by Social Media, Word of Mouth Marketing and Trust. Partially, individual Word of Mouth Marketing has no significant effect on purchasing decisions at Mutimuv Samarinda Distro. Of the three independent variables that have a dominant influence on purchasing decisions are social media variables.